Nanobiophotonics - Popescu, Gabriel (McGraw-Hill Biophotonics, 2010)
"How can we realize super resolution medical imaging using nanotechnology and optical technology. This introductory tutorial provides readers sufficient knowledge to understand this new branch of multidisciplinary study, nanobiophotonics, and further allow them to review most resent research results in the biomedical application"--Provided by publisher